2021
DOI: 10.3389/fonc.2021.627866
|View full text |Cite
|
Sign up to set email alerts
|

Identification of UL69 Gene and Protein in Cytomegalovirus-Transformed Human Mammary Epithelial Cells

Abstract: A growing body of evidence addressing the involvement of human cytomegalovirus (HCMV) in malignancies had directed attention to the oncomodulation paradigm. HCMV-DB infected human mammary epithelial cells (HMECs) in culture showed the emergence of clusters of rapidly proliferating, spheroid-shaped transformed cells named CTH (CMV-Transformed HMECs) cells. CTH cells assessment suggests a direct contribution of HCMV to oncogenesis, from key latent and lytic genes activating oncogenic pathways to fueling tumor ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Viruses with causative effects in cancer include the Epstein–Barr virus leading to Burkitt’s lymphomas [ 8 , 9 ] and human papillomavirus leading to cervical cancer [ 10 , 11 ]. Some recent studies also show that human cytomegalovirus (HCMV) has oncogenic potential where it directly leads to oncogenesis [ 12 , 13 , 14 ]. Indeed, the virus is found in cancerous tissues, including colorectal [ 15 ], prostate [ 16 ], ovarian [ 17 ] and glioblastoma cancers [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viruses with causative effects in cancer include the Epstein–Barr virus leading to Burkitt’s lymphomas [ 8 , 9 ] and human papillomavirus leading to cervical cancer [ 10 , 11 ]. Some recent studies also show that human cytomegalovirus (HCMV) has oncogenic potential where it directly leads to oncogenesis [ 12 , 13 , 14 ]. Indeed, the virus is found in cancerous tissues, including colorectal [ 15 ], prostate [ 16 ], ovarian [ 17 ] and glioblastoma cancers [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence also shows that HCMV infection plays a role in breast cancer [ 19 , 20 , 21 ]. This may be oncogenic [ 12 , 13 , 14 ] or oncomodulatory where the infection contributes to cancer progression through the alteration of intracellular signaling pathways [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Basal-like biopsies accounted for the highest percentage of biopsies with high Ki67 mRNA expression level (% of basal-like: 44%) compared to healthy (2%) and luminal biopsies (20%) ( p-value (High Ki67 - Basal : Healthy) = 0.02) ( Figure 7A ). To further study the role of HCMV associated with Ki67 transcript expression, we assessed the presence of HCMV in the biopsies by quantifying IE1 and UL69 genes using qPCR ( 21 , 30 ). In HCMV-positive biopsies, basal-like biopsies showed the highest percentage of biopsies with high levels of Ki67 mRNA (40%) in contrast to the healthy (0%) and luminal (0%) biopsies ( Figure 7B ).…”
Section: Resultsmentioning
confidence: 99%
“…The study was authorized by the local ethics committees of Besançon University Hospital (Besançon, France) and the French Research Ministry (AC-2015-2496, CNIL n°1173545, NF-S-138 96900 n°F2015). The presence of HCMV, within all the biopsies, was assessed by qPCR using IE1 and UL69 primers as mentioned above and described previously ( 30 ). For Ki67 and GAPDH mRNA quantification, RNA was extracted from the biopsies using E.Z.N.A.…”
Section: Methodsmentioning
confidence: 99%
“…Recent data showed that HCMV could perhaps induce transformation by enhancing the expression of viral genes (for example, UL69 gene). The presence of UL69 gene in CTH cell cultures and UL69 DNA in the majority of breast cancer biopsies indicates a potential significance of UL69 as a target in developing HCMV-vaccine ( 191 ). The usage of HCMV vaccines for the treatment of cancer patients generally and GBM patients in specific might be of high therapeutic value especially that HCMV has been shown to express oncomodulatory functions.…”
Section: Therapeutic Approaches In High-risk Populationsmentioning
confidence: 99%